Analisis Manajemen Strategi PT BARITO RENEWABLE ENERGY TBK (BREN) dengan Pendekatan SWOT, SPACE, BCG, IE Matrix, dan Grand Strategy Matrix - Laurance s Tansridjata (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
This study aims to evaluate the implementation of strategic management in Barito Renewables Energy Tbk (BREN) as a company operating in the renewable energy sector to support the transition toward a cleaner and more sustainable energy system. The company plays a significant role in developing geothermal energy as a stable baseload power source, contributing to national energy mix targets and carbon emission reduction. The research employs a qualitative descriptive method by examining internal and external business environments using several strategic formulation tools, including SWOT Analysis, SPACE Matrix, BCG Matrix, IE Matrix, and the Grand Strategy Matrix. The SWOT analysis reveals that the company’s primary strengths lie in its strategic geothermal assets, strong financial backing, long-term power purchase agreements ensuring revenue stability, and commitment to Environmental, Social, and Governance (ESG) principles. However, the firm also faces limitations such as high initial capital requirements, dependence on a single major buyer, and limited diversification of renewable energy sources. Externally, opportunities arise from supportive government policies, increasing demand for clean energy, and Indonesia’s abundant natural resources, while challenges include operational risks, regulatory dynamics, and intensifying competition within the renewable energy industry. The SPACE analysis positions the company in an aggressive quadrant, indicating strong capability for expansion and business development. The BCG Matrix categorizes its core business as high-growth and high-market-share, requiring sustained investment. The IE Matrix suggests a grow-and-build posture, and the Grand Strategy Matrix confirms that the company is in a strong competitive position within a rapidly growing market. Overall, the recommended strategy is sustainable growth through expanding clean energy capacity, diversifying renewable energy portfolios, leveraging technological innovation, and strengthening strategic partnerships and green financing. These strategies are expected to enhance competitiveness while supporting the long-term national energy transition agenda